THE EFFECT OF PEAK LOAD ON DEPTH OF RUTTING DURING NARROW CRACKS ON ASPHALT PAVEMENT (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2023)
The Pantoloan-Taweli road section with an Arterial Road arterial road function has a Pantoloan Port as a national logistics and goods center, as the location of the Palu Special Economic Zone (SEZ) location is estimated to have a much larger percentage of heavy vehicles and cause rutting damage to the asphalt surface, so it is necessary to know how the peak load affects the thickness of the pavement, the time of occurrence of narrow cracks, wide cracks, and 50% cracks and rutting is used Highway Development and Management (HDM) III, from CBR data and ADT pavement service life is planned for 5,10,15, and 20 years. From the results of the study, it is known that the longer the service life or the design life, the greater the peak load value where the greater the peak load value, the thicker the flexible pavement layer, and the faster the predicted that the road will crack. Effect of crack occurrence time on rutting depth (RDM) with variations in design life, i.e. the longer the design life of a road, the faster the time for narrow cracks, wide cracks, and 50% cracks, and the deeper the rutting that occus on asphalt pavements. ABSTRAK Ruas jalan Pantoloan-Tawaeli dengan fungsi jalan arteri memiliki Pelabuhan Pantoloan sebagai pusat logistik dan barang nasional, sebagai lokasi Kawasan Ekonomi Khusus (KEK) Palu yang diperkirakan presentase kendaraan beratnya jauh lebih besar dan menyebabkan kerusakan rutting pada permukaan aspal, sehingga perlu diketahui bagaimana pengaruh beban puncak terhadap tebal perkerasan, waktu terjadinya retak halus, retak lebar, dan retak 50% dan rutting, digunakan Highway Development and Manajemen (HDM) III, dari data CBR dan LHR direncanakan umur layanan 5, 10, 15 dan 20 tahun. Dari hasil penelitian diketahui bahwa semakin lama umur layanan maka nilai beban puncak akan semakin besar. dan semakin besar nilai beban puncak maka lapis perkerasan lentur yang dibutuhkan akan semakin tebal dan semakin cepat jalan tersebut diprediksi mengalami retak. Pengaruh waktu terjadi retak terhadap kedalaman rutting dengan variasi umur rencana yaitu semakin lama umur rencana maka semakin cepat waktu terjadi retak Halus (TYN), Retak Lebar, Retak 50% maka semakin dalam rutting yang terjadi pada perkerasan beraspal.